2021
DOI: 10.5209/tekn.74375
|View full text |Cite
|
Sign up to set email alerts
|

Autonomías precarias: un análisis sobre las tecnologías para personas con diversidad funcional intelectual

Abstract: Las tecnologías digitales han irrumpido en la vida de las personas con diversidad funcional con la promesa de ofrecer más autonomía y accesibilidad con logros ciertamente remarcables. La diversidad funcional intelectual, sin embargo, ha sido un campo en el que tales desarrollos han sido más modestos y presenta aún ciertas incertidumbres. La cuestión de la autonomía, concretamente, plantea problemas en su puesta en práctica, especialmente cuando se la piensa desde la idea de sujeto individual autónomo capaz de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To some extent, what this way of running the service shows is a logic of care [46], whereby caregivers only intervene from a non-imposing position, but at the same time from an active and concerned position towards the people to whom this support is provided [47]. All of this is done by means of a set of human and non-human resources, in a concrete assemblage to enable their functionality [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To some extent, what this way of running the service shows is a logic of care [46], whereby caregivers only intervene from a non-imposing position, but at the same time from an active and concerned position towards the people to whom this support is provided [47]. All of this is done by means of a set of human and non-human resources, in a concrete assemblage to enable their functionality [24].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, reasoning is not something detached from the world; we need a network of people, technologies or institutions to be able to do so. Thus, autonomy, also in the field of intellectual disability, is not only a certain capacity to decide, but a certain capacity to relate [24].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Science and technology studies have shown how the capacity to act depends on heterogeneous networks that allow certain modes of individual agency (Callon, 2008). In the case of AC, this involves the articulation of a set of more or less formal meetings with families and users, the formulation of a personal care plan, the provision of formal and informal meeting spaces, the use of furniture catalogues, certain technologies, and so on (Moyà-Köhler & Domènech, 2021; that allow the person with learning disabilities to emerge as autonomous in the process of thinking (Law, 1999) and taking decisions. In the case of CL, it entails facilitating a nonhospital space, to develop individualized plans, the promotion of community activities, and the training of assistants in the promotion of independent living.…”
Section: Tensions: Bureaucratization and Hospitalizationmentioning
confidence: 99%